(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
This contribution briefly presents the historical context of the speech in Parliament by Diego Tajani, former attorney general of the king in Palermo, in which he denounced the use of the Mafia in the management of public order. In particular, the intermingling of law enforcement and the forces of disorder is highlighted as a key-factor in the Mafia’s establishment in Sicily in the 1800s